Heterogeneity effect of central bank independence on asset prices : evidence from selected developing countries - Anwar, Cep Jandi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study analyzes the response to financial asset prices and economic activity concerning central bank independence (CBI) shocks in selected developing countries. Financial asset prices were divided into the exchange rate, bond yield, and stock price, while the analysis was contingent on a panel Vector Autoregressive estimation. Furthermore, this study identifies heterogeneity across the countries in its sample through poolability tests. This is achieved through a mean-group estimation to the panel Vector Autoregressive by averaging the PVAR coefficients and impulse response function for all individual countries. Additionally, the sample countries are divided into two sub-groups. The results showed that central bank independence reduces bond yield and increases stock price in the first two quarters. However, it takes a year to cause an appreciation in the exchange rate. Moreover, financial asset prices have an essential role in monetary policy transmission to the extent that a change in CBI affects the exchange rate, bond yield, stock price, thereby influencing private consumption and investment.